IMPLEMENTATION OF PLACEMAKING APPROACH IN LANDSCAPE DESIGN OF BARITO BRIDGE TOURISM AREA - Aina, Noor (Border: Jurnal Arsitektur, 2022)
The Barito Bridge Bottom Tourism Area is a public open space that is a tourist facility provided for tourists to see the view of the Barito Bridge. The condition of the landscape has greatly declined. To revitalise this area, a placemaking approach is used to determine the landscape design. The research method used is descriptive qualitative with the first stage assessing the existing conditions using placemaking indicators. Secondly, SWOT analysis of A4 conditions (attractions, amenity, accessibility, ancillary) so that it can determine design solutions by implementing placemaking indicators into landscape design. Through this approach, it is expected to provide recommendations for the physical components of the area as a whole. The findings of this research are that placemaking criteria can help the design of public open space landscapes, especially in tourist areas, in an effort to achieve successful placemaking.